2015
DOI: 10.1155/2015/875872
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization of Steering Mechanism for Rotary Steering System Using Modified NSGA-II and Fuzzy Set Theory

Abstract: Due to the complicated design process of gear train, optimization is a significant approach to improve design efficiency. However, the design of gear train is a complex multiobjective optimization with mixed continuous-discrete variables under numerous nonlinear constraints, and conventional optimization algorithms are not suitable to deal with such optimization problems. In this paper, based on the established dynamic model of steering mechanism for rotary steering system, the key component of which is a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Zhao et al (2018) established a steering structural parameter optimization model for an electric-hydraulic hybrid steering system and proposed a hybrid particle swarm optimization algorithm to realize global information exchange. Li et al (2015) minimized the dynamic vibration response of the steering mechanism by optimizing the structural parameters under geometric, kinematic, and strength constraints. However, the wide vibration frequency range of the vibration source makes it easy to produce unstable resonance vibration when coupled with the frequency of some of the components of the steering system; thus, parameter adjustment is required to produce a characteristic change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al (2018) established a steering structural parameter optimization model for an electric-hydraulic hybrid steering system and proposed a hybrid particle swarm optimization algorithm to realize global information exchange. Li et al (2015) minimized the dynamic vibration response of the steering mechanism by optimizing the structural parameters under geometric, kinematic, and strength constraints. However, the wide vibration frequency range of the vibration source makes it easy to produce unstable resonance vibration when coupled with the frequency of some of the components of the steering system; thus, parameter adjustment is required to produce a characteristic change.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) established a steering structural parameter optimization model for an electric–hydraulic hybrid steering system and proposed a hybrid particle swarm optimization algorithm to realize global information exchange. Li et al. (2015) minimized the dynamic vibration response of the steering mechanism by optimizing the structural parameters under geometric, kinematic, and strength constraints.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that NSGA-II obtained better optimization objective values than other methods. Li et al 17 combined NSGA-II and fuzzy set theory to optimize dynamic model of steering mechanism and got the better result than the original design. However, far too little attention has been paid to the research about multi-objective optimal design of cycloid speed reducers.…”
Section: Introductionmentioning
confidence: 99%
“…The NSGA-II algorithm was originally proposed by Deb et al [36]. It has been proved to be a highly effective and generally successful choice for optimization problems and becomes one of the mainstream solutions to multiobjective optimization questions [37][38][39].…”
Section: Introductionmentioning
confidence: 99%